1979
DOI: 10.2307/1589681
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Growth Characteristics of Psittacine Viruses in Chicken Embryos

Abstract: Eight viruses were isolated in embryonating eggs, from psittacine birds comprising a cockatiel, a budgerigar, 3 parrots, a love bird, and 2 rosellas. Initial attempts at isolation used 3 routes of embryo inoculation: yolk sac, allantoic sac, and chorioallantoic membrane (CAM). The most sensitive route was determined for 6 of the isolates by making comparative titrations by yolk sac, allantoic sac, and CAM routes of inoculation. In growth-curve studies of 6 of the isolates, virus concentration was determined da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…2A). The RSL-1 strain (ATCC VR-915) [3], which is a reference strain for PsHV-1 in this study, was detected with all five primer sets. Tomaszewski et al reported that ten patterns (PsHV-1 variants v1 to v10) were observed using these five primer sets [12].…”
mentioning
confidence: 60%
“…2A). The RSL-1 strain (ATCC VR-915) [3], which is a reference strain for PsHV-1 in this study, was detected with all five primer sets. Tomaszewski et al reported that ten patterns (PsHV-1 variants v1 to v10) were observed using these five primer sets [12].…”
mentioning
confidence: 60%
“…Stressful situations such as exposure to sudden cold weather, or moving birds to an unfamiliar location are predisposing factors for the appearance of symptoms (CHEVILLE, 1978). For this reason, disease outbreaks are commonly observed in recently imported birds (HITCHNER and HIRAI, 1978;MILLER et al, 1979;. Sudden, deadly and unrestrained outbreaks of PPD may occur after the introduction of a new presumably infected psittacine bird (MARTIN et al, 1979;MILLER et al, 1979; GOMEZ-VILLAMANDOS, 1991), but sometimes in the resident birds of a flock with no history of recent introduction of new birds (SIMPSON and HANLEY, 1977).…”
Section: Introductionmentioning
confidence: 99%